The fame thief ebook - Hallinan, Timothy (Junior Bender, 2013)
Hollywood burglar-turned-detective Junior Bender has a knotty new case to solve—a 60-year-old Tinseltown mystery There are not many people brave enough to say no to Irwin Dressler, Hollywood’s infamous mob boss-turned-movie king. Even though Dressler is ninety-three years old, Junior Bender is quaking in his boots when Dressler’s henchmen haul him in for a meeting. Dressler wants Junior to solve a “crime” he believes was committed more than seventy years ago, when an old friend of his, once-famous starlet Dolores La Marr, had her career destroyed after compromising photos were taken of her at a Las Vegas party. Dressler wants justice for Dolores and the shining career she never had. Junior can’t help but think the whole thing is a little crazy. After all, it’s been sixty years. Even if someone did set up Dolores for a fall from grace back then, they’re probably long dead. But he can’t say no to Irwin Dressler (no one can, really). So he starts digging. And what he finds is that some vendettas never die—they only get more dangerous.